Optimizing Face To Face Interactions In English Classroom Blended Learning Of Higher Education Level - Niki Raga Tantri (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2018)
This article discussed Blended Learning after the flourished utilization of Learning Management System (LMS) in English classrooms. LMS is found to be one of the efficient digital tools in delivering the content learning, especially English subject. Almost all language skills can be exploited by LMS. It provides English learning both synchronous and asynchronous modes; which meet the purpose of personalized learning. However, there still could be found that LMS has been mistakenly used and created blended learning becomes inefficient learning strategy in the classroom, mostly in face to face meetings. To tackle the problems, this paper attempts to propose the concept of face to face interactions in blended learning classroom. It will be seen from LMS’s ability in the classroom, characteristics of Generation Z students, and the demand of 21st century skills for future workforce.